Assessment of nicotine dependence in subjects with vascular dementia - Chandra, Mina; Anand, Kuljeet Singh (International Journal of Research in Medical Sciences, 2017)
Background: Nicotine dependence is an important public health issue. Nicotine dependence is a risk factor for vascular diseases like myocardial infarction and vascular dementia. The rate of nicotine dependence in Indian subjects with vascular dementia is not known. Hence we decided to assess nicotine dependence in subjects with vascular dementia. Methods: Nicotine dependence in subjects with vascular dementia was assessed among subjects presenting to memory clinic of a tertiary care hospital over a period of 16 months. Data regarding sociodemographic profile and severity of nicotine dependence as per Fagerstrom nicotine dependence scale for smoking and smokeless tobacco was analysed using SPSS version 17. Results: Our study shows that in 159 subjects with vascular dementia continuing nicotine dependence was seen in nearly 12% of the subjects. Though the rates are less than the population prevalence for India, it is still relevant as nicotine is not just a risk factor for development of vascular dementia but severe nicotine dependence and longer duration of nicotine use were found to be poor prognostic factors associated with severe dementia. Further as all subjects continued to be nicotine dependent despite having been advised to quit tobacco, suggesting the need for a more comprehensive tobacco cessation intervention be offered to subjects with vascular dementia to improve outcomes. Conclusion: In subjects with vascular dementia continuing nicotine dependence is an important risk factor which must be addressed.